Idiopathic toe walking and heterozygous mutation in the NDGR1 gene: 2 clinical cases - D. Pomarino; J. R. Tren; A. A. Emelina (Лечащий Врач)
This article describes two clinical cases of patients with tiptoe walking. As part of the diagnosis, both patients underwent a genetic test for hereditary sensorimotor neuropathy, which revealed in one patient a mutation in the NDRG1 gene with a rare variant c.1022G> A; p.arg341his (minor allele frequency < 0.01%), in the other patient a heterogeneous variant c.1053_1082del and NM_001135242.1 p.thr360_ gly369del was detected. These mutations are associated with Charcot–Marie–Toute disease (type 4D), but none of the patients were clinically diagnosed with this hereditary neuropathy, while the diagnosis of idiopathic toe-walking is also doubtful, since in both cases quite serious treatment was required. Therefore, it is reasonable to assume that both patients walk on tiptoe for a genetic reason.